2021
DOI: 10.3389/fpls.2020.617528
|View full text |Cite
|
Sign up to set email alerts
|

Using Genetic Engineering Techniques to Develop Banana Cultivars With Fusarium Wilt Resistance and Ideal Plant Architecture

Abstract: Bananas (Musa spp.) are an important fruit crop worldwide. The fungus Fusarium oxysporum f. sp. cubense (Foc), which causes Fusarium wilt, is widely regarded as one of the most damaging plant diseases. Fusarium wilt has previously devastated global banana production and continues to do so today. In addition, due to the current use of high-density banana plantations, desirable banana varieties with ideal plant architecture (IPA) possess high lodging resistance, optimum photosynthesis, and efficient water absorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 113 publications
(189 reference statements)
0
19
0
Order By: Relevance
“…Dwarfism is one of the most important objectives of banana breeding because dwarf plants have strong resistance to wind or flood disturbances (Cho et al, 2016 ; Wang et al, 2021 ). Recent work found that chemical mutagenesis is capable of inducing dwarf and semi-dwarf mutants from high-stem banana varieties (Aslam et al, 2016 ; Amosova et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dwarfism is one of the most important objectives of banana breeding because dwarf plants have strong resistance to wind or flood disturbances (Cho et al, 2016 ; Wang et al, 2021 ). Recent work found that chemical mutagenesis is capable of inducing dwarf and semi-dwarf mutants from high-stem banana varieties (Aslam et al, 2016 ; Amosova et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Plant diseases can result in up to a 40% yield loss in food crops ( Sastry and Zitter 2014 ) and genome editing technologies are providing advantages in mitigating these losses ( Sharma et al, 2021 ). Wang et al (2021) report that genome editing has been applied to improve disease resistance to fusarium wilt in bananas. Similar research is underway against fusarium wilt in Colombia ( Maxmen 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…The intensive use results in the pathogenic resistance to fungicides and an increase in environmental contamination ( Dita et al, 2018 ). No commercial varieties display an effective resistance against Foc TR4 until now ( Dale et al, 2017 ; Wang et al, 2021 ). The presence of any resistant cultivars would not exclude the use of other disease control approaches that could contribute to maintaining the resistance to pathogens over time.…”
Section: Introductionmentioning
confidence: 99%